The Result of Using Aroma Soft Doll Innovation to Relieve Stress for Nursing Students at Siam University - Takaree, Sukrita; Janthanakul , Pichaporn; Songsiri , Orntipa; Kontongthom , Thanyalakwadee; Deechatthanakun , Thanyaluk (Journal of Nursing, Siam University, 2023)
The quasi-experimental research the objective was to study the effect of using The Result of using Aroma soft doll innovation to relieve stress for nursing students. In a group of 215 moderately stressed-highly stressed students, a controlled study was conducted. Measure the results before and after the experiment. It was divided into 108 experimental groups and 107 control groups. The experiment was conducted for 4 weeks in July-December 2022. Selye theory (1976) was applied as a research conceptual framework. The instruments used in the experiment were Aroma soft doll innovation developed by the researcher tools used to collect data consisted of a stress assessment form of the Department of Mental Health (SPST-20), a questionnaire on the use of Aroma soft doll innovation and the satisfaction questionnaire on the use of Aroma soft doll innovation had a validity of 0.85, 0.83, 0.86 and 0.83 with a reliability of 0.85, 0.78, 0.71, and 0.67, respectively. Descriptive data were analyzed using percentage, mean, and statistics. Standard deviation the results were compared with the t-test and the correlation was analyzed using Pearson’s correlation coefficient. The results showed that: The Result of using Aroma soft doll innovation to relieve stress for nursing students of the experimental group was significantly lower than the control group at 0.05. Factors that affected the stress of nursing students with statistical significance (p < 0.01) were family factors followed by economic factors theoretical study and relationship (p < 0.05).